SPACE DISTRIBUTION AND LARVAE HABITATS OF THE AEDES AEGYPTI IN THE DEPARTMENT OF ANTIOQUIA. 1990 - LÓPEZ-A., YOLANDA LUCÍA; WOLFF-E., MARTHA ISABEL; ESCOBAR-V., JOSÉ PABLO; OSORIO-Q., LISARDO (Revista Colombiana de Entomología, 1992)
Due to the emergency presented with the first case of Dengue Hemorrhagic Fever in Puerto Berrio (Antioquia, Colombia), and the following outbreak of Dengue Hemorrhagic Fever in other regions of the state and the country, the Public Health Service of Antioquia, from January through May 1990, began the Plan for Surveillance and Control of Aedes aegypti in the state. This Plan required to update the spatial distribution of the vector and to know the most endangered areas for the transmission of Dengue according to the larval index in houses and containers. It was found that 66.1% of the states' cities and towns are infected with the insect and they are located between O and 2.000 m.a.s.l. Tanks (48.4%), water cans (17.5%), and tires (12.8%) were founds as the main larval habitats used by A. aegypti. It was found that the deficit of water supply and the community habits influence the predominance of certain kinds of containers as the main A. aegypti larvae habitats. The Bajo Cauca, Urabá, Magdalena Medio, and Porce-Nus regions were found as high-risk areas for Dengue virus transmission due to the high infestation index.